2009
DOI: 10.1038/jp.2009.36
|View full text |Cite
|
Sign up to set email alerts
|

Early amino acids and the metabolic response of ELBW infants (⩽1000 g) in three time periods

Abstract: Objective: To evaluate early amino-acid (AA) administration in extremely low birth weight (ELBW) infants over three time periods, beginning with the initiation of this strategy. Study design:This was a retrospective study of ELBW infants between 2000 and 2007. Nutritional intake and laboratory results were monitored during the first 5 days of life. Growth rates and complications were followed until discharge.Result: Infants were similar in birth weight (BW), gestational age (GA) and severity of illness. The ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…18 Our findings of the importance of the type of calories supplied for in-hospital preterm growth have been emphasized by other investigators. [14][15][16][24][25][26][27][28][29][30] In 1998, Carlson and Zeigler 24 published a longitudinal study of 51 preterm infants and their protein intake, energy intake and subsequent growth. Regression analysis suggested that protein intake related positively to growth.…”
Section: Discussionmentioning
confidence: 99%
“…18 Our findings of the importance of the type of calories supplied for in-hospital preterm growth have been emphasized by other investigators. [14][15][16][24][25][26][27][28][29][30] In 1998, Carlson and Zeigler 24 published a longitudinal study of 51 preterm infants and their protein intake, energy intake and subsequent growth. Regression analysis suggested that protein intake related positively to growth.…”
Section: Discussionmentioning
confidence: 99%
“…Radmacher demonstrated a modest increase in urea as the AA dose was increased. 9 Blanco demonstrated higher urea levels in the early high amino acid (EHAA) group as compared with the standard amino acid (SAA) group during the first week of life. 13 Braake showed that in conjunction with the higher blood urea nitrogen (BUN) levels, the higher amounts of excreted nitrogen in the EHAA group indicated a higher oxidation rate.…”
Section: Discussionmentioning
confidence: 99%
“…8 Early administration of AA has been shown to be safe and promotes positive nitrogen balance in preterm infants. 2,9 Some authors have studied the relationship of EPN with the weight gain in preterm infants. A prospective study by Valentine et al compared 308 preterm VLBW infants who received EPN supplementation with 132 infants who did not receive EPN.…”
Section: Discussionmentioning
confidence: 99%
“…They also found there to be no relationship between BUN and protein intake. 24 There are several randomized controlled trials that have evaluated the effects of protein administration in VLBW infants and which have found early administration of amino acids to be well tolerated. Wilson et al randomized 125 VLBW infants to an aggressive parenteral and enteral nutritional regimen (goal protein load of 2.5 to 3.5 g/kg/day) versus a controlled conservative nutritional regimen (goal protein load of 2.5 g/kg/day).…”
Section: Discussionmentioning
confidence: 99%